The implementation of mnemonic learning method in enhancing retention of ilmu sorrof - Wijaya, Mualim; Setiyawati, Febriani Risqi Nur; Goda, Saleh Sawky Hassan (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
Ilmu Sorrof consists of numerous linguistic components, making it challenging for students to learn and understand. This difficulty is further compounded when teachers rely solely on lecture and rote memorization methods, which often lead to student boredom and hinder comprehension and memorization of the material. As a solution to these challenges in teaching Ilmu Sorrof, the mnemonic learning method offers a quick and effective approach to understanding and memorizing the subject. This study aims to describe the implementation of the mnemonic learning method in improving the retention of Ilmu Sorrof. The research employs a qualitative case study approach conducted in the 7th-grade language program at SMP Nurul Jadid Paiton Probolinggo. Data collection techniques include observation, interviews, and documentation. Data analysis is carried out through data collection, data condensation, and conclusion drawing. The results show that the mnemonic learning method facilitates easier recall and comprehension in the teaching of Ilmu Sorrof.